2020
DOI: 10.1029/2019jc015934
|View full text |Cite
|
Sign up to set email alerts
|

Arctic and Antarctic Sea Ice Mean State in the Community Earth System Model Version 2 and the Influence of Atmospheric Chemistry

Abstract: Arctic and Antarctic sea ice has undergone significant and rapid change with the changing climate. Here, we present preindustrial and historical results from the newly released Community Earth System Model Version 2 (CESM2) to assess the Arctic and Antarctic sea ice. Two configurations of the CESM2 are available that differ only in their atmospheric model top and the inclusion of comprehensive atmospheric chemistry, including prognostic aerosols. The CESM2 configuration with comprehensive atmospheric chemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 72 publications
2
43
0
Order By: Relevance
“…Locally, however, Lenaerts et al (2020) found that CAM6 simulated excessive rainfall over the coastal GrIS in the modern era relative to observationally validated regional model data, which is likely linked to the CAM6 cloud liquid sedimentation issue we present here. DuVivier et al (2020) found that CESM2-CAM6 modern era simulations substantially underestimate both Arctic sea ice volume and sea ice extent relative to observationally based estimates. Similarly,…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 90%
See 1 more Smart Citation
“…Locally, however, Lenaerts et al (2020) found that CAM6 simulated excessive rainfall over the coastal GrIS in the modern era relative to observationally validated regional model data, which is likely linked to the CAM6 cloud liquid sedimentation issue we present here. DuVivier et al (2020) found that CESM2-CAM6 modern era simulations substantially underestimate both Arctic sea ice volume and sea ice extent relative to observationally based estimates. Similarly,…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 90%
“…DuVivier et al. (2020) found that CESM2‐CAM6 modern era simulations substantially underestimate both Arctic sea ice volume and sea ice extent relative to observationally based estimates. Similarly, DeRepentigny et al.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the CESM2(CAM6) September ice area is consistently lower than observed (Figure 1a), with too little ice in the Pacific and Eurasian sectors of the Arctic (Figures 2a–2c). DuVivier et al (2020) found that differences in ice area already exist between CESM2(CAM6) and CESM2(WACCM6) in their preindustrial control simulations, with the largest differences in the summer months. These discrepancies in ice area and volume can be attributed to thinner early spring clouds in the CESM2(CAM6), which drive a strong ice‐albedo feedback and result in a lower ice area in September and significantly thinner ice year‐round (DuVivier et al, 2020).…”
Section: Historical Arctic Sea Icementioning
confidence: 99%
“…We note that this difference in phase is hinted at in Figure 4a but is not as obvious perhaps because the apparent amplitude difference is dominant. This phase difference also appears (but is not discussed) in the monthly analysis carried out by DuVivier et al (2020). They show that sea ice retreat in the CESM2 begins in October rather than September.…”
Section: Resultsmentioning
confidence: 77%
“…The sea ice regions used in this analysis (Figure 1) were defined by Raphael and Hobbs (2014) and are based on coherent spatial variability in the SIC field. DuVivier et al (2020) assesses the seasonal distribution of SIC simulated by the CESM2. They show that the model does a credible job of simulating the distribution of SIC.…”
Section: Methodsmentioning
confidence: 99%